Quaqtaq : modernity and identity in an Inuit community - Dorais, Louis-Jacques, 1945- (University of Toronto Press, 1997)
Comprises an ethnographic study of the small, predominantly Inuit village of Quaqtaq in Nunavik in arctic Quebec. The author focuses on the interaction between modernity and tradition in residents' relations with the outside world and, more specifically, in cultural identity. Includes a few b & w photographs.